Reconceptualization of Ideal Islamic Bankers in The Sharia Framework (An Effort to Create a Sharia Compliance Ecosystem) - Hidayatullah, Muhammad Syarif; Azhari, Fathurrahman; Yusuf, Mahmud; Fadillah, Rahmat (Fakultas Agama Islam Universitas Muhammadiyah Yogyakarta, 2024)
Islamic bankers have a central position and an essential role in the implementation of Sharia principles in Islamic banking practices because Islamic bankers are parties directly related to the operational implementation of Sharia contracts. This research attempted to reconceptualize the figure of the Islamic banker with the formulation of the ideal Islamic banker within the framework of Sharia norms. This research was qualitative research that applied a literature study. Referring to the Hadith of the Prophet, Atsar Umar bin Khattab and Qaul Abu Laits, which serve as the foundation for the formulation of the ideal Islamic banker in the ideas of banking jurisprudence related to Islamic Human Resources Management, Islamic bank management must consider the relevance of education in selecting employees as an application of the Islamic recruitment model. Furthermore, the ideal Islamic banker will be realized through Islamic training, which forms ways of thinking, competence, character, and work motivation within the Sharia framework. The results indicated that Islamic bankers had adequate knowledge of Sharia and enthusiasm and commitment, which was vital in implementing all Sharia provisions in banking transactions to create a Sharia compliance ecosystem in Islamic banking.